Analysis of Public Service Bureaucracy Reform at the One-Stop Investment and Integrated Services Office, Maluku Province, Indonesia - Zainal Abidin Rengifurwarin (International Journal of Science and Society, 2019)
Public service bureaucracy reform is one of the important and strategic issues of its nature, absolutely necessary to produce an effective organizational profile, concise management, and professional HR. One of the reform efforts undertaken by the government and regional government is to establish the One-Stop Integrated Investment and Services Office (DPMPTSP) of Maluku Province, with the aim of improving the performance of licensing services. The purpose of this study was to analyze the performance of the public service bureaucracy and public service bureaucratic reform in the Maluku Province DPMPTSP. This research approach is a quantitative descriptive survey. The respondents of this research were the leaders and employees of the Public Licensing service sub-sector, which numbered 19 people. Data collection uses observation techniques, questionnaires, and interviews. The results of this research indicate that the performance of the licensing service process affects the performance of the results, and both of these service performance is influenced by public service bureaucratic reforms carried out in Maluku Province DPMPTSP.